Pengaruh Kedalaman Stemming Terhadap Distribusi Fragmentasi Hasil Peledakan Batuan di Tambang Batu Gamping PT Semen Indonesia (Persero) - Amirullah Nur (Fakultas Teknik, 2026)
Limestone is one of the non-metallic industrial excavation materials. The potential of limestone is very much found throughout Indonesia. Limestone can be used by carrying out the mining process. PT Semen Indonesia (Persero) Tbk is one of the limestone mining companies in the cement industry located in Tuban Regency, East Java Province. The mining system used at PT Semen Indonesia (Persero) Tbk is an open pit mining system (surface mining) using the "Quarry" open mining method for non-metallic mining. One of the mining activities carried out at PT Semen Indonesia (Persero) Tbk is by carrying out blasting activities. The activity aims to dismantle the material so that the fragmentation becomes small according to the size expected by the company. The purpose of this study is to analyze the results of fragmentation in the blasting method. Data processing on actual blast fragmentation uses image analysis and Kuz-Ram methods obtained from three different blocks. The results of the image analysis obtained a retained percentage of 60% of block N-13, 63% block H-16, and 50% block I-15. Meanwhile, in the Kuz-Ram method, 75% of the N-13 block, 72% of the H-16 block, and 69% of the I-15 block were obtained. It can be seen that the percentage of pass in the actual blast still does not meet the target, so it is necessary to design the stemming depth using the R.L-ash theory to determine the optimal geometry. and the results of the fragmentation of the proposed blast using the Kuz-Ram theoryof <15% on each proposal. So that the proposed blasting has a better fragmentation result than the actual blasting.
Finalisasi file repositori 16 Juli 2026_Kurnadi Validasi dan Finalisasi Ratna 17 Juli 2026
Keywords: Stemming; Peledakan Batuan; Distribusi Fragmentasi